Electron beam induced epitaxial crystallization in a conducting and insulating a-LaAlO3/SrTiO3 system. Issue 64 (17th August 2017) - Lee, Gwangyeob; Moon, Seon Young; Kim, Jinyeon; Baek, Seung-Hyub; Kim, Do Hyang; Jang, Ho Won; Chang, Hye Jung
Abstract : We report the effect of the interfacial conductivity on the e-beam-induced crystallization of an oxide a-LaAlO3 thin film on the SrTiO3 substrate and the kinetics can be controlled by the electrical conductivity of the interface and the dose rate. Abstract : Interfacial conductivity at the interface between two insulating oxides, that is 2DEG, shows a number of intriguing properties and applications, such as on/off switching with external electric fields, use in nanoscale electronic devices and tunable conductivity. Here, we report the effect of the interfacial conductivity on the kinetic behavior of electron-beam-induced epitaxial crystallization of an oxide amorphous thin film on an SrTiO3 substrate. Epitaxial growth from the interface can occur without direct e-beam irradiation at the interface due to accumulated charge around the beam position in the insulating materials. 2DEG, which acts as a current path delays the crystallization kinetics, thus delicate control of the crystallized pattern shape and size is available. As a result, successful pattern writing with a width of about 5 nm was performed. The present work provides useful guidelines for coherent atomic scale e-beam patterning considering the critical distance of the electron beam from the interface for the epitaxial growth, e-beam dose rate effect on the growth rate and the heterostructure interfacial conductivity.